PERTANGGUNGJAWABAN ATAS PENGGUNAAN DISKRESI OLEH PEJABAT PEMERINTAH DARI SUDUT PANDANG HUKUM ADMINISTRASI NEGARA - Muhammad Khaerul Luthfi (JURNAL ILMIAH NUSANTARA, 2024)
Central and regional governments have free will over their positions, and their actions impact their positions within the government area in question. On the other hand, officials in private areas are only responsible for their positions as long as statutory regulations give them the authority. Thus, almost every country based on law has a government that is responsible for serving the community and is accountable to all its citizens. This research is normative research, the approach used is a statutory regulation approach and a conceptual approach. The results of this research are (1) In general, policy regulations give officials the authority to issue policies without going through the legislative process. These regulations must not deviate from or conflict with the rules above and must not arbitrarily violate the human rights or obligations of citizens. This regulation also remains valid within the scope of the law and general principles of good governance; (2). Because this authority cannot be separated and is part of the designated position, this responsibility falls directly on government officials who carry out discretionary actions. Thus, when the office holder then takes action, they will experience the related juridical consequences. When there are elements of maladministration, such as abuse of authority, and officials act in the name of their position, they have official responsibilities. A person can be held criminally responsible for actions carried out by government officials if they have malicious intent, for example, using their authority intentionally to obtain benefits for themselves, other people, or companies, resulting in financial losses to the state.